ANALYSIS THE RELATIONSHIP OF LEVEL OF POVERTY AGAINST THE NUMBER OF RESIDENTS IN THE PROVINCE LAMPUNG 2013 (ISTECH Journal (International Science And Technology Journal), 2018)
Growth the population is one important factor in the problem the social economy generally and the population problem in particular. Because the amount and composition of the population will also affect the condition social economy of a region or country or the world. The problem employment, unemployment, and poverty have become a problem trees of this race and need handling immediately. In order not to be a hindrance Indonesia to make the Country developed. In addition to the support of the community is important. If in a the community groups trying to reduce the level of poverty that there is, of course, the government will be more convenient for other problems. Each individual should have the attitude of conscious and perceptive of the problems there, the specifics of his problem of poverty. Still high his floor poverty in Lampung make the government to more optimizing the effort is done. To help penangangan level of poverty, then be able to do the analysis relationship between the level of poverty by the total population in the Province of Lampung. In this research using the data of the level of poverty and the amount of the population of the Year 2013. Its purpose is to help the government as material consideration in the reduce level of poverty in Province Lampung. Based on the results of the analysis acquired: level of poverty and the total population had a relationship a strong where the relationship is positive ,which means if the total population increases then the level of poverty will increasingly rose. As well as the obtained regression model : Y= -5153 + 0,1563 X. From the results of the analysis variansi the total population contributed 81,74% against the level of poverty. While the rest of 18,26% affected by other factors that are not accounted into the model.